A terahertz-driven non-equilibrium phase transition in a room temperature atomic vapour - C. G. Wade (Nature Portfolio, 2018)
The nonlinear interaction between terahertz frequency electric fields and atoms or molecules can be used to study fundamental and technical problems. Here the authors demonstrate a THz–driven phase transition, with a potential application as a THz sensor, using Rydberg atomic states in a cesium vapor.